Stress-tuned spin wave modes in magnetic vortex nanoellipses for flexible magnonic systems - Saavedra-Díaz, E (ELSEVIER, 2026)
Using micromagnetic simulations, we investigated the effects of mechanical stress and nanostructure size variations on the spin wave modes in Galfenol nanoellipses with a vortex-like magnetic configuration. Our results indicate that both the frequency spectrum and the spatial distribution of the modes are influenced by the type of applied stress (tensile or compressive) and by the nanostructure size. In particular, the modes tend to display regions of maximum oscillation amplitude along the direction of the applied tensile stress. For structures with a circular geometry, the frequency spectrum as a function of mechanical stress is symmetric, meaning that the frequencies obtained under tensile stress have the same values as those obtained under an equivalent compressive stress. Variations in geometry, nanostructure size, and stress magnitude can also lead to the emergence of new hybrid modes with both radial and azimuthal components, while the overall vortex profile remains largely unchanged. These findings illustrate a method for controlling spin wave modes in nanostructures with non-trivial magnetic configurations, such as magnetic vortices, through mechanical stress, opening up numerous possibilities for applications in flexible magnonic systems.